Warehouse Layout Evaluation using the Activity Method Relationship Chart to Maximize Capacity and Efficiency Material Storage - Bahiy Handayaningrat; Andyas Mukti Pradanarka (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2026)
Partner companies from various industrial sectors often face issues related to warehouse operational efficiency, particularly in managing suboptimal facility layouts. At PT PLN Nusantara Power UP Paiton, this issue is evident in the inefficient flow of materials within the warehouse, resulting in operational delays and increased costs. This report aims to evaluate the warehouse layout using the Activity Relationship Chart (ARC) method to maximize capacity and material storage efficiency. The ARC method is used to analyze the proximity relationships between facilities in a warehouse based on existing operational processes. The evaluation is conducted by comparing the initial layout with proposed alternative layouts, with a focus on optimizing material flow, reducing moving distances, and increasing warehouse operational efficiency. The analysis results show that the proposed alternative layout can improve warehouse space efficiency, reduce material movement distance, and accelerate workflow. The application of the ARC method successfully identified areas for improvement to increase productivity and reduce material management time. Evaluation of warehouse layout using the ARC method can significantly contribute to improving operational efficiency and better warehouse management at PT PLN Nusantara Power UP Paiton. It is recommended to continue implementing this method in improving the layout of other facilities to support smooth operations and reduce company costs.